MEMAKNAI ZAKAT PROFESI DAN PERHITUNGANNYA - Komala Dewi; Fauziah nur Hutauruk; Yadi Islami (Jurnal Pemberdayaan Masyarakat, 2024)
Zakat is a mandatory worship for all Muslims who are financially able and have reached the minimum limit for paying zakat or called nisab. Zakat is a certain portion of wealth that must be paid by every Muslim if they have met the specified requirements. As one of the pillars of Islam, Zakat is paid to be given to groups who are entitled to receive it (asnaf). In terms of language, zakat means clean (cleansing oneself), holy (purifying oneself), blessing and growing. Zakat comes from the word "zaka" which means holy, good, blessing, growing, and growing. It is called zakat because it contains the hope of obtaining blessings, cleansing the soul and nurturing it with various goodness (Fiqh Sunnah, Sayyid Sabiq: 5). This zakat has many benefits, both for individuals and for society. Therefore, let's pay professional zakat sincerely and with full awareness so that our wealth becomes a blessing and useful for others.